PARTISIPASI MASYARAKAT DAIAM PEMBANGUNAN DI DESA MILINGGAME KECAMATAN TIOMNERI KABUPATEN LANNY JAYA PROPINSI PAPUA - WENDA, NERANUS; Pangkey, Masje Silija; Londa, Very (Sam Ratulangi University, 2015)
ABSTRACT: This study departed from the indication of the low participation of villagers / villageMilinggame Tiomneri District in the process of rural development. Questions / research problems to beaddressed are: (1) how the level of public participation in decision making processes in their villagedevelopment program; (2) how the level of participation of rural communities / villages Milinggame inthe implementation process in their village development program.The method used is descriptive method .. Respondents many as 58 heads of family were taken atrandom side (random) of as many as 520 households in the village Milinggame. Collecting data usingquestionnaires / questionnaire and assisted with interview techniques. The analysis technique used isdescriptive analysis (analysis of frequency distribution and percentages).The result showed: (1) In terms of indicators used it turns out most of the respondents have neverparticipated in the decision-making process of development programs in rural / village; (2) In terms ofindicators used it turns out most of the respondents have never participated in the implementation ofdevelopment programs in rural / village.Based on the results of the study conclusion: (1) Public participation Rural / Village Milinggame in thedecision making process for rural development programs / villages are generally low; (2) Publicparticipation Rural / Village Milinggame in the process of implementation / execution of developmentprograms, rural / village generally low.Departing from the conclusions of these studies it is suggested: Necessary efforts are moreeffective to increase community participation Village / Village Milinggame District Tiomneri in theprocess of rural development, such as: providing information / counseling or motivation to thecommunity, to optimize the role of community institutions (LPM, PKK, and others) in the construction ofthe village / town, enhancing the role of social organizations / religious in mobilizing communityparticipation, and optimize the implementation of democracy in the preparation of developmentprograms in rural / village.Keywords: community participation, rural development.